2017
DOI: 10.1534/g3.116.037333
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis ofDrosophila melanogasterThird Instar Larval Ring Glands Points to Novel Functions and Uncovers a Cytochrome p450 Required for Development

Abstract: In Drosophila melanogaster larvae, the ring gland (RG) is a control center that orchestrates major developmental transitions. It is a composite organ, consisting of the prothoracic gland, the corpus allatum, and the corpora cardiaca, each of which synthesizes and secretes a different hormone. Until now, the RG’s broader developmental roles beyond endocrine secretion have not been explored. RNA sequencing and analysis of a new transcriptome resource from D. melanogaster wandering third instar larval RGs has pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 91 publications
1
57
0
1
Order By: Relevance
“…Nevertheless, Cyp6t3 is not enriched in any of the three detoxification tissues and so may not be a detoxification gene. Additionally, Cyp6g2 (DS = 1) is an interesting case, as its proposed role in juvenile hormone synthesis (Christesen et al, 2016) and corpora allata-specific expression (Chung et al, 2009) are at odds with its ability to detoxify multiple insecticides when ectopically expressed in detoxification tissues (Daborn et al, 2007; Denecke et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, Cyp6t3 is not enriched in any of the three detoxification tissues and so may not be a detoxification gene. Additionally, Cyp6g2 (DS = 1) is an interesting case, as its proposed role in juvenile hormone synthesis (Christesen et al, 2016) and corpora allata-specific expression (Chung et al, 2009) are at odds with its ability to detoxify multiple insecticides when ectopically expressed in detoxification tissues (Daborn et al, 2007; Denecke et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…There is experimental evidence that some P450 genes in D. melanogaster belong to multiple functional classes. Cyp6g2 (DS = 1) may be involved in juvenile hormone metabolism (Christesen et al, 2016), but also has the capacity to detoxify multiple classes of insecticides if expressed ectopically (Daborn et al, 2007; Denecke et al, 2017). Cyp6g2 is a paralog of Cyp6g1 (DS = 4), which encodes a detoxification enzyme with very broad substrate specificity (Battlay et al, 2018; 2016; Daborn et al, 2002; 2007; Fusetto et al, 2017; Joußen et al, 2008; J.…”
Section: Discussionmentioning
confidence: 99%
“…Increased ploidy of prothoracic gland cells is important for optimal expression of steroidogenic genes and can be induced by activation of the Torso/MAPK pathway (Ohhara et al, 2017;Shimell et al, 2018). Because the genes required for ecdysone biosynthesis are among the most abundantly expressed in the prothoracic gland, their mRNA levels may be entirely limited by gene copy number (Christesen et al, 2017;Fox and Duronio, 2013). A similar requirement for copy number amplification to produce peak gene expression levels has been observed in other cell types in Drosophila, including chorion gene expression in ovarian follicle cells (Orr-Weaver, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In laboratory strains Cyp6g2 is specifically expressed in the corpus allatum within the ring gland 40 and is implicated in the synthesis of juvenile hormone 41 . However, ectopic expression of this gene in digestive tissues showed that it was able to confer resistance to nitenpyram and diazinon 32 .…”
Section: Discussionmentioning
confidence: 99%